Epileptic Encephalopathy and Cerebellar Atrophy Resulting from Compound Heterozygous CACNA2D2 Variants - Kameryn M. Butler; Philip J. Holt; Sarah S. Milla; Cristina da Silva; John J. Alexander; Andrew Escayg (Case Reports in Genetics)
CACNA2D2 encodes an auxiliary subunit of the voltage-dependent calcium channel. To date, there have only been two reports of individuals with early-infantile epileptic encephalopathy due to CACNA2D2 mutations. In both reports, patients were homozygous for the identified variants. Here, we report a patient with epileptic encephalopathy and cerebellar atrophy who was found to have two novel variants in the CACNA2D2 gene: c.782C>T (p.Pro261Leu) and c.3137T>C (p.Leu1046Pro), by whole-exome sequencing. The variants were shown to be inherited in trans and the unaffected parents were confirmed to be heterozygous carriers. This is the third report of recessive CACNA2D2 variants associated with disease and the first report of compound heterozygous variants. The clinical description of this new case highlights the phenotypic similarities amongst individuals with CACNA2D2-related disease and suggests that CACNA2D2 should be considered as a differential diagnosis in individuals with cerebellar dysfunction and multiple seizure types that begin in the first year of life.